COVID- 19 PANDEMIC AND THE PROTECTION OF THE RIGHT TO ABORTION (EU and comparative law issues and challenges series (ECLIC), 2021)
The COVID - 19 pandemic that swept the world in 2020 and the reactions of state authorities to it are unparalleled events in modern history. In order to protect public health, states have limited a number of fundamental human rights that individuals have in accordance with national constitutions and international conventions. The focus of this paper is the right of access to abortion in the Member States of the European Union. In Europe, the situation with regard to the recognition of women's right to abortion is quite clear. All member states of the European Union, with the exception of Poland and Malta, recognize the rather liberal right of a woman to have an abortion in a certain period of time after conception. However, Malta and Poland, as members of the European Union, since abortion is seen as a service, must not hinder the travel of women abroad to have an abortion, nor restrict information on the provision of abortion services in other countries. In 2020, a pandemic highlighted all the weaknesses of this regime by preventing women from traveling to more liberal countries to perform abortions, thus calling into question their right to choose and protect their sexual and reproductive rights. This is not only the case in Poland and Malta, but also in countries that recognize the right to abortion but make it conditional on certain non-medical conditions, such as compulsory counselling; and the mandatory time period between applying for and performing an abortion; in situations present in certain countries where the problem of a woman exercising the right to abortion is a large number of doctors who do not provide this service based on their right to conscience. The paper is divided into three parts. The aim of the first part of the paper is to consider all the legal difficulties that women face in accessing abortion during the COVID -19 pandemic, restrictions that affect the protection of their dignity, right to life, privacy and right to equality. In the second part of the paper particular attention will be paid to the illiberal tendencies present in this period in some countries of Central and Eastern Europe, especially Poland. In the third part of the paper, emphasis will be put on the situation in Malta where there is a complete ban on abortion even in the case when the life of a pregnant woman is in danger.